2014
DOI: 10.1155/2014/969404
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Responsive Genes Overlap with Triiodothyronine-Responsive Genes in a Breast Carcinoma Cell Line

Abstract: It has been well established that estrogen plays an important role in the progression and treatment of breast cancer. However, the role of triiodothyronine (T3) remains controversial. We have previously shown its capacity to stimulate the development of positive estrogen receptor breast carcinoma, induce the expression of genes (PR, TGF-alpha) normally stimulated by estradiol (E2), and suppress genes (TGF-beta) normally inhibited by E2. Since T3 regulates growth hormones, metabolism, and differentiation, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…1 and 2). These results correlate with studies that demonstrated increased expression of a number of genes, such as amphiregulin (AREG) in MCF7 cells [40], leptin in adipocytes 3T3-L1 cells [41], and HIF1A in human fibroblast cells [39], upon treatment with T 3 . Taken together, these results show that T 3 affects the transcription of HIF1A and TGFA at both short periods of time.…”
Section: Discussionsupporting
confidence: 89%
“…1 and 2). These results correlate with studies that demonstrated increased expression of a number of genes, such as amphiregulin (AREG) in MCF7 cells [40], leptin in adipocytes 3T3-L1 cells [41], and HIF1A in human fibroblast cells [39], upon treatment with T 3 . Taken together, these results show that T 3 affects the transcription of HIF1A and TGFA at both short periods of time.…”
Section: Discussionsupporting
confidence: 89%
“…These receptors act by binding specific DNA sequences called estrogen response elements (EREs) and thyroid response elements (TREs) within the regulatory regions of target genes [4,5] . Evidence of cross-talk between TH and E2 has been reported in past decades [6] in different experimental systems such as kidney [7] , neural [8,9] , thyroid [10] , and breast tumor [11][12][13] cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated that both T4 and T3 lead quickly (within hours) to an expression of an array of anti-apoptotic genes in tumor cells, thus supporting cancer development. 2,5,6,13,[15][16][17][18]22,[25][26][27][28][29] In a recent work from our group, we documented an inhibitory effect by thyroid hormones on the expression of six genes associated with tumor suppression (GDF-15, 30 IGFBP-6 13,31 ), apoptosis (Nix, PUMA 32 ), and cell cycle regulation (p21, p16 33,34 ), in ovarian cancer cell lines. 13 In the current study, we have extended our research to a panel The majority of the genes examined were downregulated by the hormones.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this previous publication we have established that thyroid hormones play a regulatory role in the transcription of αvβ3 integrin subunits (monomers) and of certain additional genes involved in tumor suppression, cell cycle inhibition and mitochondrial apoptosis. 13 Given the fact that thyroid hormones effects on transcription can be initiated nongenomically through the thyroid-αvβ3 axis, 2,13,[15][16][17][18] we extended our analysis to fifteen cancer-relevant genes, whose expression is regulated by the nongenomically initiated actions of thyroid hormones. We also defined the involvement of the MAPK and PI3K signaling pathways to these effects of T4 and T3.…”
mentioning
confidence: 99%